2022
DOI: 10.1007/s10826-022-02347-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Wellbeing, Dyadic Adjustment, and Parental Stress among Spanish Families during the COVID-19 Outbreak

Abstract: Due to COVID-19, many countries, like Spain, imposed lockdown on the entire population to prevent the virus from spreading. The purpose of this exploratory study is to investigate the severity of psychological symptoms, dyadic adjustment, and parental stress of parents during the first three weeks of the outbreak. It also aims to identify several risk factors that contribute to this distress. A total of 727 parents completed a form on an online platform with sociodemographic data, BSI- 18, EAD-13, and the Span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…For example, positive psychologists propose that it is possible for individuals to report positive mental health, even during highly stressful circumstances, and that being able to identify positive aspects of life during COVID-19 may lead to beneficial outcomes (Waters et al, 2021(Waters et al, , 2022. Indeed, previous studies demonstrate that parents who identified more rewards of the pandemic also experienced greater parental satisfaction and fewer stress symptoms (Aramburu et al, 2022;Herbert et al, 2020). A more nuanced understanding of this complex narrative may be critical to better supporting parents under extreme stress or during future public health crises.…”
mentioning
confidence: 99%
“…For example, positive psychologists propose that it is possible for individuals to report positive mental health, even during highly stressful circumstances, and that being able to identify positive aspects of life during COVID-19 may lead to beneficial outcomes (Waters et al, 2021(Waters et al, , 2022. Indeed, previous studies demonstrate that parents who identified more rewards of the pandemic also experienced greater parental satisfaction and fewer stress symptoms (Aramburu et al, 2022;Herbert et al, 2020). A more nuanced understanding of this complex narrative may be critical to better supporting parents under extreme stress or during future public health crises.…”
mentioning
confidence: 99%